A Systemic View of Psychological Consultation in Schools - Brown, Jacob E. (Canadian Journal of Counselling and Psychotherapy, 2011)
Psychological consultation in school has often emphasized intervention with an individual consultée who then deals with the client. This general approach has largely ignored advances in systemic understanding of human behaviour. This paper argues that change is facilitated when the wider system which directly influences and is influenced by the student is considered. Interventions for a maximum effect are delivered in consulting sessions, where school officials and/or family members are present with the student. The paper discusses various interventions and the situations which influence their appropriateness. Case studies are presented to illustrate this application of a systemic view.